Changes in attitudes toward diabetes in nursing students at diabetes camp. Issue 4 (7th March 2021) - Moran, Vicki; Blanchette, Julia; Whitley, Heather; Pillion, Dennis; Albritton, Anna; Israel, Heidi
Abstract: Aim: The research purpose was to determine whether exposure to residential diabetes camps affects attitudes toward diabetes care and management in nursing students. Background: Summer camp for children with type 1 diabetes mellitus (T1D) provides a unique and engaging clinical environment for nursing students to learn about evolving diabetes care and to help children develop diabetes management skills. Methods: This prospective, pretest/posttest study assessed student nurses' attitudes about diabetes, who attended one of four residential summer camps in the United States, using the Diabetes Attitude Survey 3 (DAS3). The survey was administered before and after clinical experience designed to fulfill experiential curricula requirements from various nursing programs. Results: After attending diabetes camp, nursing students ( N = 73) had a positive change in their attitudes regarding the need for special training and the psychosocial impact of diabetes. Discussion: The diabetes camp clinical experience impacted nursing students' attitudes. Diabetes camps are a unique clinical setting that uses learned clinical knowledge and judgment to promote health and prevent disease and disability, supporting the integration of primary care and public health nursing.